Fatty Acid Composition of Echium amoenum Fisch et. Mey. Seeds (Boraginaceae) - F Mojab; A Behfar; F Kobarfard; B Nickavar; B Ja'fari (Institue of Medicinal Plants, ACECR, 2009)
Background: The seeds of Echium amoenum (Boraginaceae) are used in Iranian Traditional Medicine as diuretic, analgesic, hypotensive and diaphoretic. Objective: This study was designed to identification and quantification of composition of fatty acids in the seeds oil of E. amoenum. Methods: The seeds of the plant were extracted with n-hexane. After evaporating under reduced pressure, oil was get. Methanolysis of the oil glyceride was carried out in KOH medium and BF3, under reflux condition for 30 min. The esters passed into the upper hexane layer, then analyzed by GC-MS. Results: The seeds of E. amoenum revealed the presence of four fatty acids including one saturated and three unsaturated. Conclusion: The unsaturated fatty acids were present in much greater proportion than saturated ones. Linolenic acid was found to be major unsaturated fatty acid and the palmitic acid as predominant saturated acid.